Opportunity of Applying Clean Production in UMKM (SMBs) Badminton Racket at Malang City - Bambang Ismuyanto (Natural B, Journal of Health and Environmental Sciences, 2011)
Small medium enterprise badminton racket in Malang consume water wastefully. Rinse water discharged into river and causing pollution problem. In fact, rinse water can still be utilized. Rinse water can be reused for anodizing other racket. The results showed that the rinse water could be used five times and the impact on saving electricity and water resources. Rinse water used to anodize produced products that are not much different if the new rinse water is used.